Analysis of Incoterms and Relational Resources to Improve Competitive Advantage: A Study of Freight Forwarders Company in Indonesia - Sugiono, Ahmad; Rahayu, Agus; Wibowo, Lili Adi; Hurriyati, Ratih (Asian Journal of Logistics Management, 2023)
This study aims to analyze the impact of Incoterm and relational resources on the competitive advantage of Indonesian Freight forwarders. The measurement methodology uses structural equation model (SEM) analysis with SmartPLS software to analyze the impact of Incoterms and relational resources on competitive advantage. Through social media, online questionnaires were sent to gather research data. The Likert scale of 5 was used to create the questionnaire. Companies that provide freight forwarding services were the respondents in this study, chosen by simple random sampling. Online questionnaires were distributed to 75 companies to answer questions submitted. The data analysis step is validity tests, reliability tests, significance tests, and hypothesis tests. Based on the data processing results, it is found that Incoterm and relational resources positively affect competitive advantages. The novelty of this study is a model of the relationship between the effect of Incoterm and relational resources on the competitive advantage of freight forwarding companies. The research's theoretical implication is that Freight forwarder companies' management should select appropriate incoterms and implement relational resource policies to encourage increased competitive advantage. One of the limitations of this study is that the sample size used is only a small number of companies engaged in international Freight Forwarder services, only 75 companies.